Moringa oleifera leaf ethanol extract immunomodulatory activity discriminates between chronic myeloid leukaemia cell line and normal lymphocytes - Lawal, Hamza; Al-Graittee, Satar Jabbar Rahi; Ranggasamy, Ramesh; Sarmadi, Vahid Hosseinpour; Thambiah, Subashini C.; Stanlas, Johnson; Ramasamy, Rajesh (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Moringa oleifera, a member of the family Moringaceae, is a small-medium sized tree, widely cultivated in Southeast Asia, Polynesia, and the West Indies, where the leaves, fruits and flowers form part of their routine diet. The plant has been reported to possess numerous pharmacological properties; however, its immunomodulatory po- tentials were least explored, especially on lymphocytes. Therefore, this study aimed to investigate the in vitro immu- nomodulatory effect of Moringa oleifera leaves’ ethanol extract (MOETE) on transformed and normal lymphocytes, the leukaemic cell line BV173 and healthy peripheral blood mononuclear cells (PBMCs), respectively. Methods: The freshly collected and dried Moringa oleifera leaves were extracted using 70% ethanol, and the cytotoxicity activity on transformed and normal lymphocytes was determined using an MTT assay. The immunomodulatory effect was further evaluated through cell proliferation assays, cell cycle analysis and apoptosis assays. Results: The ethanolic extract of Moringa oleifera leaves showed concentration-dependent cytotoxic effects on the BV173 cell line with an IC50 of 125±6 µg/mL while exerting a stimulatory effect on PBMCs (EC50 = 28±3 µg/mL). The extract also exerted antiproliferative effects, cell cycle arrest and apoptosis in the BV173 tumour cell but enhanced the viability and proliferation of PBMCs by committing the cells into the cell cycle and reducing apoptosis despite stimulation by phytohemagglutinin (PHA). Conclusion: The MOETE has immunostimulatory properties on normal lymphocytes and anti-tumour activity on the leukaemic cell lines.